Understanding Utilization of Basic Oral Health Services Through the Health Belief Model: A Population-Based Study in Kediri, East Java, Indonesia - Galih Reza Firmansyah; Arsita Eka Prasetyawati; Endang Sutisna Sulaeman; Erindra Budi Cahyanto; Selfi Handayani (Journal of Health Promotion and Behavior, 2026)
Background: The utilization of basic oral and dental health services remains suboptimal despite the availability of services within primary healthcare systems. This gap suggests that service utilization is influenced not only by access but also by individual health beliefs and perceptions. The Health Belief Model provides a theoretical framework to explain how cognitive and behavioral factors shape health-seeking behavior. This study aimed to examine determinants of basic oral health service utilization in Kediri Regency, Indonesia, using the Health Belief Model framework. Subjects and Method: A cross-sectional study was conducted among 363 residents of Kediri Regency selected through multistage sampling. The dependent variable was the utilization of basic oral and dental health services. Independent variables included perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action. Data were collected using structured questionnaires and analyzed using multiple logistic regression with a significance level of p < 0.005. Results: Perceived benefits showed a positive and significant association (OR = 1.30; 95% CI: 0.71 to 2.44; p = 0.037), cues to action demonstrated a significant negative association (OR = 0.59; 95% CI: 0.31 to 1.13; p = 0.012), perceived susceptibility (OR = 2.42; 95% CI: 0.90 to 6.48; p = 0.074), perceived severity (OR = 0.84; 95% CI: 0.41–1.72; p = 0.062), perceived barriers (OR = 0.71; 95% CI: −0.41 to 1.22; p = 0.228), and self-efficacy (OR = 1.86; 95% CI: −0.82 to 4.37; p = 0.146) were not statistically significant predictors of dental service utilization. Conclusion: Utilization of basic oral health services was primarily influenced by perceived benefits and cues to action. Strengthening public awareness of the benefits of dental care and enhancing behavioral triggers may improve the utilization of oral health services in the community.